AB0922 UPDATES ON THE EVIDENCE BASED INTERDISCIPLINARY GUIDELINES FOR HENOCH-SCHöNLEIN PURPURA. (June 2019) - Abu-Zaid, Mohammed Hassan; Miedany, Yasser El; Hassan, Waleed; Farag, Yomna; Lotfy, Hala; Eissa, Mervat; Mortada, Mohammed A.; Nasef, Samah Ismail; Mekkawy, Dalia; Deriny, Ghada El; Gaafary, Maha El; Atef, Yossra; et al.
Abstract : Background: Henoch-Schönlein purpura (HSP) is the most common childhood vasculitis, it is characterized by inflammation of small vessels leading to non-thrombocytopenic purpura, arthritis/arthralgia, GI hemorrhage and glomerulonephritis 1 . There is a very poor evidence base to guide the management of HSP, particularly for those with the severe forms of HSP nephritis, Up till now there are no EULAR or ACR recommendations for management of HSP. Objectives: To set an updated interdisciplinary recommendations for the management of HSP Methods: Interdisciplinary guidelines were developed with representative from PRINTO Egypt for pediatric rheumatology as well as patients' group. A systemic literature analysis in MEDLINE was performed, evidence and recommendations were graded, an algorithm for treatment and final statements were discussed in a consensus meeting (Nominal Group Technique). A preliminary draft was fine tuned and discussed thereafter by all participants (Delphi Procedure). Results: Consensus was reached on recommendations, including a standardized treatment strategy according to the HSP severity state in the individual patient. In this updated interdisciplinary guideline for HSP; treatment was tailored to the patient's pathology and its severity (figure 1 ). Criteria for admission were identified as: severe arthritis or arthralgia limiting ability to weight bearing and mobilization, severe abdominal pain, GI hemorrhage, evidence of nephritis/nephritic syndrome or renal impairment, evidence of neurological symptoms. Criteria for early referral to pediatric nephrologist were also identified including: hypertension, abnormal renal function, macroscopic hematuria for 5-days, nephrotic syndrome, acute nephritic syndrome, as well as persistent proteinuria. Conclusion: A total of seven evidence based interdisciplinary recommendations for management of HSP have been formulated, that provide an up-to-date guidance of HSP management. Reference: [1] Hetland LE, Susrud KS, Lindahl KH, Bygum A. Henoch-Schönlein Purpura: A Literature Review. Acta Derm Venereol. 2017Nov15;97(10):1160-1166. doi: 10.2340/00015555-2733. Disclosure of Interests: None declared